Allicin, an Antioxidant and Neuroprotective Agent, Ameliorates Cognitive Impairment - Muhammad Shahid Nadeem; Imran Kazmi; Inam Ullah; Khushi Muhammad; Firoz Anwar (MDPI AG, 2021)
Allicin (diallylthiosulfinate) is a defense molecule produced by cellular contents of garlic (Allium sativum L.). On tissue damage, the non-proteinogenic amino acid alliin (S-allylcysteine sulfoxide) is converted to allicin in an enzyme-mediated process catalysed by alliinase. Allicin is hydrophobic in nature, can efficiently cross the cellular membranes and behaves as a reactive sulfur species (RSS) inside the cells. It is physiologically active molecule with the ability to oxidise the thiol groups of glutathione and between cysteine residues in proteins. Allicin has shown anticancer, antimicrobial, antioxidant properties and also serves as an efficient therapeutic agent against cardiovascular diseases. In this context, the present review describes allicin as an antioxidant, and neuroprotective molecule that can ameliorate the cognitive abilities in case of neurodegenerative and neuropsychological disorders. As an antioxidant, allicin fights the reactive oxygen species (ROS) by downregulation of NOX (NADPH oxidizing) enzymes, it can directly interact to reduce the cellular levels of different types of ROS produced by a variety of peroxidases. Most of the neuroprotective actions of allicin are mediated via redox-dependent pathways. Allicin inhibits neuroinflammation by suppressing the ROS production, inhibition of TLR4/MyD88/NF-κB, P38 and JNK pathways. As an inhibitor of cholinesterase and (AChE) and butyrylcholinesterase (BuChE) it can be applied to manage the Alzheimer's disease, helps to maintain the balance of neurotransmitters in case of autism spectrum disorder (ASD) and attention deficit hyperactive syndrome (ADHD). In case of acute traumatic spinal cord injury (SCI) allicin protects neuron damage by regulating inflammation, apoptosis and promoting the expression levels of Nrf2 (nuclear factor erythroid 2-related factor 2). Metal induced neurodegeneration can also be attenuated and cognitive abilities of patients suffering from neurological diseases can be ameliorates by allicin administration.